TOTAL PERFORMANCE SCORECARD INNOVATION FOR IMPROVING EDUCATIONAL QUALITY AT SD NEGERI 61 BANDA ACEH - Ida Fazila; Sariakin; Syarfuni (Paedagogia: Jurnal Pendidikan, 2024)
This research aims to develop a strategic planning model based on the Total Performance Scorecard (TPS) to enhance educational quality. The research method employed is developmental research involving analysis, design, development, implementation, and model evaluation. The study addresses challenges in formulating school strategic plans that currently do not meet theoretical standards and lack synchronization among plan components. Findings indicate suboptimal alignment with theoretical standards and lack of synchronization among plan components, reflecting minimal involvement from school stakeholders. As a solution, a TPS-based strategic planning model was developed involving all educators to fill out Personal Balanced Scorecards, while administrative staff filled out Organizational Balanced Scorecards. Discussions involving supervisors, school inspectors, and the school committee through Focus Group Discussions produced a SWOT analysis used to formulate the school's vision, mission, goals, objectives, key roles, strategies, and programs for the next five years. Implementation of this model will occur following operational and theoretical validation in the field, with plans to develop TPS-based strategic plans by 2028. Implications of the research highlight the importance of strengthening the strategic planning process at SD Negeri 61 to align more closely with theoretical standards and integrate plan components. Active engagement of all school stakeholders is expected to improve understanding and acceptance of the strategic plan, ensuring that the school's vision, mission, goals, and strategies reflect their needs and aspirations. The development of this model is anticipated to effectively address educational dynamics and future challenges, enabling the school to play a more optimal role in enhancing educational quality.